Fabel dalam Bingkai Sastra: - Besse Darmawati (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2013)
This research aims to describe the critics on human attitude in fables along with their existence asa critic media in Buginese society. The researcher applies descriptive-qualitative method through electical approach. The techniques of research are identification, note, observation, and analysis. A number of Buginese folklores in a book entitled Sastra Lisan Bugis published by Educational and Cultural Department in 1981 contain the population of research. The research samples are taken purposively as the data. The fables used as data are (1) Buaya dan Kerbau; (2) Pelanduk dan Macan; (3) Putteang dan Karoakkak; and (4) Rusa dan Kura-Kura. Based on the analysis,the researcher found some critics on human attitudes like greed, stupidness, fear, revenge, lie, andarrogance. These attitudes are still found in Buginese society